The Impact of Urban Spatial Structure on Travel Demand in the United States - Bento, Antonio M.; Cropper, Maureen L.; Mobarak, Ahmed Mushfiq; Vinha, Katja (World Bank, Washington, DC, 2014)
The authors combine measures of urban form and public transit supply for 114 urbanized areas with the 1990 Nationwide Personal Transportation Survey to address two questions: (1) How do measures of urban form, including city shape, road density, the spatial distribution of population, and jobs-housing balance affect the annual miles driven and commute mode choices of U.S. households? (2) How does the supply of public transportation (annual route miles supplied and availability of transit stops) affect miles driven and commute mode choice? The authors find that jobs-housing balance, population centrality, and rail miles supplied significantly reduce the probability of driving to work in cities with some rail transit. Population centrality and jobs-housing balance have a significant impact on annual household vehicle miles traveled (VMT), as do city shape, road density, and (in rail cities) annual rail route miles supplied. The elasticity of VMT with respect to each variable is small, on the order of 0.10-0.20 in absolute value. However, changing several measures of form simultaneously can reduce annual VMT significantly. Moving the sample households from a city with the characteristics of Atlanta to a city with the characteristics of Boston reduces annual VMT by 25 percent.